Quality of Life, Depression, and Anxiety in Patients Undergoing Renal Replacement Therapies in Saudi Arabia - Emad Adel Shdaifat (The Scientific World Journal)
Despite improvements in renal replacement therapy (RRT) for end-stage renal disease (ESRD), it continues to have serious negative impacts on quality of life (QOL) and emotional status. This study determines the association between demographic characteristics and the negative emotional states of depression, anxiety, and stress in Saudi Arabia. A comparative cross-sectional study was conducted in the Eastern Region of Saudi Arabia. Convenience sampling was used to recruit participants comprising hemodialysis (HD), peritoneal dialysis (PD), and kidney transplantation (Tx) patients. They completed the Short Form-36 Survey and the Depression, Anxiety, Stress Scale (DASS). The physical component summary (PCS) score was similar for HD (41.7) and PD (41.5), but higher among Tx (45.2). The mental component summary (MCS) score was similar between HD (48.0) and Tx (48.8), but lower in PD (42.3). The majority of patients in all groups had normal levels of depression, anxiety, and stress. Overall, the study found that PCS was higher among Tx patients compared to HD and PD, while MCS was higher among HD and Tx patients than PD patients. Most patients’ levels of depression, anxiety, and stress were within the normal range. Those findings will provide policymakers and health managers with the significant factors which can affect the QOL of dialysis and Tx patients.